PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI BALAI HIPERKES DAN KESELAMATAN KERJA PROVINSI KALIMANTAN SELATAN - Defin Shahrial Putra; Farida Yulianti; Lamsah - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This study aims to examine: (1) simultaneous influence of reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy) and tangibles (physical evidence) toward customer satisfaction Corporate Hygiene & Health (Hiperkes) and Safety Center, South Kalimantan Province, (2) partial effect of reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy), tangibles (physical evidence) toward customer satisfaction Corporate Hygiene & Health (Hiperkes) and Safety Center,South Kalimantan Province (3) dominant influence of reliability (Reliability) toward customer satisfaction Corporate Hygiene & Health (Hiperkes) and Safety Center,South Kalimantan Province.The population of the study is all customers who use facilities in Corporate Hygiene & Health (Hiperkes) and Safety Center,South Kalimantan Province, and this study uses random sampling technique, which samples consist of 60 companies which later analyzed using multiple linear regression data analysis.The results show 1) reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy) and tangible (physical evidence) significantly affects customer satisfaction in Corporate Hygiene & Health (Hiperkes) and Safety Center,South Kalimantan Province.2) partially, assurance (assurance), empathy (empathy) significantly affects customer satisfaction in the Central Hiperkes andSafety South Kalimantan province, while the reliability (reliability), responsiveness (responsiveness) and tangible (physical evidence) do not have significant effect toward customer satisfaction in Corporate Hygiene & Health (Hiperkes) and Safety Center,South Kalimantan Province.3) Assurance (assurance) has dominant influence toward customer satisfaction in Corporate Hygiene & Health (Hiperkes) and Safety Center,South Kalimantan Province.